The role of radio integrated marketing communication - Van Rheede van Oudtshoorn, G. P.; Mulder, Dalme (University of the Free State, 2001)
Radio, the oldest broadcasting medium, is still a hugely popular medium reaching more than eighty five per cent of the South African population. Radio's output is intimate, friendly and approachable rather than glamorous. Compared to television, radio is inexpensive to produce. It has been around so long and is so well trusted that it is in the happy but difficult position of being taken for granted. It has been said that the explosion in media choice leaves consumers with less time to spend with "old" media. Marketers are slowly but surely beginning to appreciate the qualities that make radio an excellent choice in any integrated marketing communication program.
Keywords: Integrated marketing communication (IMC); Radio; Broadcasting